Zionism and the roads not taken : Rawidowicz, Kaplan, Kohn - Pianko, Noam (Modern Jewish experience (Bloomington, Ind.), 2010)
Today, Zionism is understood as a national movement whose primary historical goal was the establishment of a Jewish state. However, Zionism's association with national sovereignty was not foreordained. Zionism and the Roads Not Taken uncovers the thought of three key interwar Jewish intellectuals who defined Zionism's central mission as challenging the model of a sovereign nation-state: historian Simon Rawidowicz, religious thinker Mordecai Kaplan, and political theorist Hans Kohn. Although their models d.